Circularly Polarized Light Probes Excited‐State Delocalization in Rectangular Ladder‐type Pentaphenyl Helices. Issue 2 (2nd December 2022) - Ammenhäuser, Robin; Klein, Patrick; Schmid, Eva; Streicher, Sabrina; Vogelsang, Jan; Lehmann, Christian W.; Lupton, John M.; Meskers, Stefan C. J.; Scherf, Ullrich
Abstract: Ladder‐type pentaphenyl chromophores have a rigid, planar π‐system and show bright fluorescence featuring pronounced vibrational structure. Such moieties are ideal for studying interchromophoric interactions and delocalization of electronic excitations. We report the synthesis of helical polymers with a rigid square structure based on spiro‐linked ladder‐type pentaphenyl units. The variation of circular dichroism with increasing chain length provides direct evidence for delocalization of electronic excitations over at least 10 monomeric units. The change in the degree of circular polarization of the fluorescence across the vibronic side bands shows that vibrational motion can localize the excitation dynamically to almost one single unit through breakdown of the Born‐Oppenheimer approximation. The dynamic conversion between delocalized and localized excited states provides a new paradigm for interpreting circular dichroism in helical polymers such as proteins and polynucleic acids. Abstract : Rectangular π‐conjugated ladder polymers of one particular handedness provide a square answer to the question of delocalization of their lowest‐energy photoexcitation: the coupling to vibrations makes the excitation shaky. Exciton localization is a dynamic process and the excitation "breathes" in concert with the zero‐point vibrational motion.